Road User Charges Model - Archondo-Callao, Rodrigo S. (World Bank, Washington, DC, 2012)
This technical note presents a road user charges model, developed by the Bank, and, gives an overview of the objectives, structure, and results of the model by taking as an example a hypothetical road network, and presenting some lessons learned, while applying the model in developing countries. The model estimates revenues from road user charges as collected by the following instruments: diesel levy; gasoline levy; alcohol levy (wherever applicable); annual license fees; annual load damage fees, and tolls. Conclusions suggest the model has proven to be a useful tool for an aggregate assessment of the entire road network of a country, both in terms of network maintenance, and the financing side. Moreover, the model is particularly useful to set road user charges, as a dedicated revenue source for a proposed road fund.